Characterization of unsaponifiable matter in F 8 genotype of opium poppy (Papaver somniferum) - BANERJI, R; DIXIT, B S; SHUKLA, S; SINGH, S P (The Indian Journal of Agricultural Sciences, 2013)
The unsaponifiable matter of F8 sgenotype of Papaver somniferum x P setigerum, analysed by gas chromatographymass spectrometry (GC-MS), was found to contain 18 constituents. Cholesterol, cholestanol, campesterol, stigmasterol,delta5.campesterol, sitosterol, delta5-avenasterol were identified which constituted 90.5% of the total unsaponifiables. Sitosterol was found to be the major constituent (59.2%), while cholestanol was found to be 4.9%. Besides sterols,alpha-tocopherol and alpha-tocotrienol were also identified. The genotype is first of its kind.